Min-Max Robust Emergency Service System Design - Janacek, Jaroslav; Kvet, Marek (Communications - Scientific letters of the University of Zilina, 2016)
This paper deals with the emergency service system design using the weighted p-median problem formulation. In such systems, not only the disutility of an average user is minimized, but also the disutility of the worst situated users must be taken into account. To cope with both objectives, we suggest a composed method. In the first phase, the disutility of the worst situated user is minimized. The second phase is based on the min-sum approach to optimize the average user’s disutility. To formulate the mathematical models, the radial approach is used mainly for its excellent performance characteristics. Within this paper, we concentrate on effective usage of the radial approach to develop an algorithm for robust emergency service system design. A robust service system design is usually performed so that the design complies with specified scenarios so that the maximal objective function value of the individual instances corresponding with particular scenarios is minimized. To find the value paid for making the system resistant to catastrophic events, a new conception called the price of robustness is introduced.